2008
DOI: 10.1016/j.exphem.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel competitive repopulation strategy to quantitate engraftment of ex vivo manipulated murine marrow cells in submyeloablated hosts

Abstract: Objective-Standard competitive repopulation assays have proven valuable in evaluating engraftment potential in ablated hosts, permitting comparisons between various test cell populations. However, no similar method exists to compare engraftment of test cells in submyeloablated hosts, which would be helpful given the applications of reduced-intensity conditioning for hematopoietic gene-replacement therapy and other cellular therapies. Here, we developed a novel assay to quantitate engraftment of hematopoietic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…We previously showed that ex vivo cultur for gamma-retroviral transduction results in decreased HSC engraftment in submyeloablated hosts [1, 18], and developed a novel competitive repopulation assay in submyeloablated hosts to quantify the engraftment defect [2]. Engraftment impairment, however, is not limited to submyeloablated hosts; the long-term repopulating ability of lin - marrow cultured for gamma-retroviral transduction, with or without exposure to gamma-retroviral supernatant, is also ~10-fold lower than that of fresh lin - marrow in ablated hosts (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that ex vivo cultur for gamma-retroviral transduction results in decreased HSC engraftment in submyeloablated hosts [1, 18], and developed a novel competitive repopulation assay in submyeloablated hosts to quantify the engraftment defect [2]. Engraftment impairment, however, is not limited to submyeloablated hosts; the long-term repopulating ability of lin - marrow cultured for gamma-retroviral transduction, with or without exposure to gamma-retroviral supernatant, is also ~10-fold lower than that of fresh lin - marrow in ablated hosts (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Gamma-retroviral transduction was performed as previously described [2] as adapted from Li and colleagues [17]. Briefly, lineage depleted marrow was prepared using a mouse Lineage Cell Depletion kit and VarioMACS apparatus (Miltenyi Biotec, Auburn, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Competitive repopulation experiments were performed by co-injecting into the dorsal tail vein of the irradiated recipients equal numbers of unmanupulated mArt -/- B6 HSC or mArt -/- B6 HSC from animals which had been previously injected with 4×10 5 BALB/c PCT-4 STC 24 hours earlier, combined with naïve WT BALB/c bone marrow cells [25]. At 2 and 4 months post transplant, peripheral blood was obtained from the lateral saphenous vein of the recipients and stained by using fluorescently conjugated antibodies to BALB/c (anti-H-2 d ) and B6 (anti-H-2 b )[16].…”
Section: Methodsmentioning
confidence: 99%